Effect of transplanted oligodendrocyte precursor cells derived from inflammatory and non-inflammatory microenvironment on remyelination in a chronic cuprizone model - Hoda Akbari; Iraj Ragerdi-Kashani; Farzaneh Rezaei-Yazdi; Parichehr Pasbakhsh (PLoS ONE, 2026)
Introduction Multiple sclerosis is a chronic demyelinating disease of the central nervous system. Transplantation of oligodendrocyte progenitor cells (OPCs) is a promising approach to enhance remyelination; however, the influence of the OPCs’ microenvironmental origin on their therapeutic efficacy remains unclear. This study compared the remyelinating capacity of OPCs isolated from inflammatory (lipopolysaccharide) and non-inflammatory (cuprizone) microenvironments after transplanting into the corpus callosum and examined their effects on extracellular matrix chondroitin sulfate proteoglycans (CSPGs). Methods OPCs were isolated from two microenvironments and characterized by immunocytochemistry and RT-qPCR. After transplanting, OPC homing, remyelination, gene expression, and CSPG levels were evaluated using DiI labeling, LFB staining, RT-qPCR, and immunofluorescence, respectively. Results Severe demyelination exhibited in the cuprizone group compared with healthy controls (p < 0.001) by Luxol fast blue staining. Myelin content significantly increased in both transplating OPCs groups (p < 0.001), with a higher impact observed in mice received OPCs isolated from cuprizone as compared with lipopolysaccharide (p < 0.001). Also, RT-qPCR analysis exhibited significantly reduced MBP expression in the cuprizone group, whereas was significantly increased after OPC transplantation, particularly in the cuprizone-derived OPC group (p < 0.001), whereas a lower increased with lipopolysaccharide-derived OPCs (p < 0.01). MOG expression exhibited a same pattern, with a significantly increase in the cuprizone-derived OPC group compared with both the cuprizone and lipopolysaccharide-derived OPC groups (p < 0.001). Additionally, Immunofluorescence analysis exhibited increasing CSPG4 levels in the cuprizone group, but significantly reduced after OPC transplantation (p < 0.001). Notably, in the cuprizone-derived OPC group higher reduction of CSPG4 levels observed compare with in the lipopolysaccharide-derived OPC group (p < 0.001). Conclusion OPC transplantation improves remyelination and reduces the CSPG level, but the effectiveness is more related to the previous history of the OPC isolation microenvironment and the new donor.